2012
DOI: 10.1186/1756-0500-5-160
|View full text |Cite
|
Sign up to set email alerts
|

Early results of systematic drug susceptibility testing in pulmonary tuberculosis retreatment cases in Cameroon

Abstract: BackgroundThe number of pulmonary tuberculosis (PTB) patients reported with resistance to first-line anti-tuberculosis drugs after a standardized retreatment regimen in Cameroon is increasing. Hence, the National Tuberculosis Control Program (NTP) implemented, in one of the ten Regions of the country, a pilot programme aimed at performing routine drug susceptibility testing (DST) for previously treated PTB cases. The objectives of the programme were to evaluate the feasibility of monitoring drug resistance amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…This was slightly lower (6.67%) than that reported by Assam-Assam et al [17]. Noeske et al [22] reported a 51% of resistance to one or more anti-TB drugs and a 12% MDR rate, among smear positive pulmonary TB re-treatment patients in the Littoral region of Cameroon. MDR-TB from other regions of the world ranges from to 12% - 37% in previously treated cases and 2.1% - 12% in newly diagnosed cases respectively in regions of the Americas, Western Pacific, and European regions [5].…”
Section: Discussionmentioning
confidence: 61%
“…This was slightly lower (6.67%) than that reported by Assam-Assam et al [17]. Noeske et al [22] reported a 51% of resistance to one or more anti-TB drugs and a 12% MDR rate, among smear positive pulmonary TB re-treatment patients in the Littoral region of Cameroon. MDR-TB from other regions of the world ranges from to 12% - 37% in previously treated cases and 2.1% - 12% in newly diagnosed cases respectively in regions of the Americas, Western Pacific, and European regions [5].…”
Section: Discussionmentioning
confidence: 61%
“… New and PT patients 416 28.7 1.3 LJ INH, RMP, SM, EMB Ellis Awusu-Dabo et al [ 44 ] 2001-2004 Ghana National survey. New and PT patients 216 25.9 4.7 INH, RMP, SM, EMB, Thiacetazone Jurgen Noesk et al [ 45 ] 2012 Cameroon Sub-national. Twenty-nine TB health facilities in Litoral region.…”
Section: Resultsmentioning
confidence: 99%
“…Multidrug-resistance (MDR) was observed only in the South region where it was detected in 1.58% (1/63) isolates. No resistance was recorded for ethambutol (EMB) in the two regions [38,39].…”
Section: Drug Sensitivity Of Tb Isolates and The Emergence Of Mdr In mentioning
confidence: 99%